Nor Sue Lae : The Lahu Musical Instrument - นุตสาระ, ธนพชร (Community and Social Development Journal, 2018)
Nor Sue Lae : A Lahu Musical Instrument, that is the part of Lahu Music and Modern Socialized Culture in Mae Na Toeng Sub-district, Pai District, Mae Hong Son Province. This article is a qualitative research by using ethnomusicology methodology. The objectives of this study were Nor Sue Lae : A Lahu musical instrument. The study Nor Sue Lae : A Lahu musical instrument was found that Nor Sue Lae is a kind of wind musical instrument. It has free reed in a Khan family. It is made from the gourd in ivory shape. The pipe and the reed are made from bamboo, using the bee’s wax to caulk the seam to prevent the inside wind out. There are has many sizes; it depend on the size of the gourd. The tuning system had 7 notes and there are E A B C E F. It had E-E and C-C to be an octaves. The all of Nor Sue Lae sounds was depended on the ears of Nor Sue Lae maker. The blow of Nor Sue Lae can do melody, harmony and drone. All the songs use in festival and it has 13 songs. The songs has short melody and play repeatedly. La-Hu song divided 3 kinds; 1) courtship song 2) about the blessing and 3) the way of life adapt for Ja-khoe dance. Nor Sue Lae is very importance musical instrument for ritual and festival of La-Hu ethic group. The La-Hu dance with Ja-khoe dance all night until the morning, especially, New Year day or “Kin-Wo”